ECLAC: Brazil, Argentina and the Problems and Mistakes in the Latin American Structuralist Economic Theory: - Paranaiba, Adriano; D'Andrea, Fernando Antonio Monteiro Christoph; Vaz-Curado, Samuel Fernandes Lucena (Revista de Economia Mackenzie, 2023)
To a large part, Latin American economic thought is rooted in the view that the State should be the engine of economic development. The theory developed by the Latin American Structuralist School supports this view. ECLAC, a United Nations development commission, is the bastion of the policy agenda branch of structuralism. Despite their central role in Latin American economic policies, structuralist ideas have hardly been discussed. We trace the historical origins of this school and use the theoretical standpoint of the Austrian School of Economics to talk about its views and mistakes.